1981
DOI: 10.1136/sti.57.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulins in the cerebrospinal fluid of patients with late syphilis.

Abstract: The concentrations of immunoglobulins G, A, and M were measured in 62 samples of cerebrospinal fluid from 35 patients with asymptomatic neurosyphilis, 18 with symptomatic neurosyphilis, and nine with late syphilis of other organs. The most frequent and highest increase in IgG and IgA occurred in patients with symptomatic neurosyphilis. IgM was found in only five patients, but its presence, together with an increase in IgG and IgA concentrations, appears to indicate activity of the pathological process and a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Retrospective calculation of Q lim is not feasible from this data. The same applies to the study from Gibowski and Machonko, who showed raised IgA concentrations in the CSF of 37 out of 62 patients with late syphilis [8]. They reported that the most frequent and highest increase in IgG and IgA occurred in patients with symptomatic neurosyphilis.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Retrospective calculation of Q lim is not feasible from this data. The same applies to the study from Gibowski and Machonko, who showed raised IgA concentrations in the CSF of 37 out of 62 patients with late syphilis [8]. They reported that the most frequent and highest increase in IgG and IgA occurred in patients with symptomatic neurosyphilis.…”
Section: Discussionmentioning
confidence: 55%
“…They reported that the most frequent and highest increase in IgG and IgA occurred in patients with symptomatic neurosyphilis. IgM was found in only a few patients, but its presence, together with an increase in IgG and IgA concentrations, appeared to indicate activity of the pathological process and a poor prognosis for the course of the disease [8]. Because in one of our patients intrathecal IgA synthesis disappeared 15 months after therapy, one could speculate that IgA is an indicator of symptomatic infection within the last year.…”
Section: Discussionmentioning
confidence: 90%
“…4 and negative FTA-ABS in all 4 patients. DISCUSSION Elevated immunoglobulin levels in CSF have been reported repeatedly in neurosyphilis (6,7,23) and also in early syphilis (31). Floden (5) reported increased globulin values in CSF in 30% of patients with secondary syphilis.…”
Section: Table III Pretreatment Results Of Wr Vdrl Fta-abs and Tpi In...mentioning
confidence: 76%